Assessment of pharmacists' delivery of public health services in rural and urban areas in Iowa and North Dakota - Scott DM; Strand M; Undem T; Anderson G; Clarens A; liu X. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: The profession of pharmacy is expanding its involvement in public health, but few studies have examined pharmacists' delivery of public health services. Objective: To assess Iowa and North Dakota pharmacists' practices, frequency of public health service delivery, level of involvement in achieving the essential services of public health, and barriers to expansion of public health services in rural and urban areas. Methods: This study implemented an on-line survey sent to all pharmacists currently practicing pharmacy in Iowa and North Dakota. Results: Overall, 602 valid responses were analyzed, 297 in rural areas and 305 in urban areas. Three practice settings (chain stores [169, 28.2%], independent community pharmacies [162, 27.0%], and hospital pharmacies [156, 26.0%]) comprised 81.2% of the sample. Both chain and independent community pharmacists were more commonly located in rural areas than in urban areas (P<0.05). For some public health services, pharmacists in rural areas reported higher frequency of delivery than did pharmacists in urban areas (P < .05) that included: medication therapy management, immunizations, tobacco counseling, and medication take-back programs. For some essential services, pharmacists (particularly independents) in rural areas reported more frequent delivery than did pharmacists in urban areas (P < .05), these included: evaluate the services the pharmacy provides, partner with the community to identify and help solve health problems, and conduct needs assessments to identify health risks in my community. Conclusion: Rural pharmacists more frequently deliver public health services than urban in both Iowa and North Dakota. These findings should be interpreted to be primarily due to differences in the role of the rural pharmacist and the quest for certain opportunities that rural pharmacists are seeking.